2007
DOI: 10.1093/ecam/nem010
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Aqueous Extract of Pleurotus pulmonarius (Fr.) Quel‐Champ. with Glyburide in Alloxan Induced Diabetic Mice

Abstract: Mushrooms are low calorie food with very little fat and are highly suitable for obese persons. With no starch and very low sugars, they are the ‘delight of the diabetics’. Combination of herbal drugs (or isolated phytochemicals) is found to be beneficial in certain diseases when given along with conventional drugs. The aim of the present study was to evaluate the effects of aqueous extract of Pleurotus pulmonarius (Lentinaceae) (called as PP-aqu) and its interaction with glyburide in alloxan induced diabetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 47 publications
1
23
1
Order By: Relevance
“…An orally administered hot water extract of P. pulmonarius had a significant antihyperglycemic effect, halted the progression of diabetes and reduced the mortality of alloxan induced diabetic mice by approximately 50%. It showed a synergistic effect with the antidiabetic drug glibenclamide, supporting the possibility of effective combination therapy of glibenclamide and P. pulmonarius for diabetes (Badole, 2008). P. pulmonarius have antimicrobial properties and exhibit antioxidant activity also (Ramesh and Pattar, 2010).…”
Section: Introductionmentioning
confidence: 70%
“…An orally administered hot water extract of P. pulmonarius had a significant antihyperglycemic effect, halted the progression of diabetes and reduced the mortality of alloxan induced diabetic mice by approximately 50%. It showed a synergistic effect with the antidiabetic drug glibenclamide, supporting the possibility of effective combination therapy of glibenclamide and P. pulmonarius for diabetes (Badole, 2008). P. pulmonarius have antimicrobial properties and exhibit antioxidant activity also (Ramesh and Pattar, 2010).…”
Section: Introductionmentioning
confidence: 70%
“…In this context, other medicinal plants, such as Cassia auriculata (Latha and Pari, 2003). Pleurotus pulmonarius (Badole et al, 2000) have been reported to possess similar effects. Flavonoids, alkaloids, tannins and phenolics are the other bioactive principles reported to possess antihyperglycaemic activity.…”
Section: Leavesmentioning
confidence: 96%
“…Feeding of mushroom powder increases the excretion of total lipids and cholesterol through fecal matter. Mevinolin (a statin: Present in fruiting bodies of P. ostreatus and P. citrinopileatus) exhibited antihypocholesterolemic activities [54,55]. P. pulmonarius exhibited potent.…”
Section: Antilipidemic Activitymentioning
confidence: 99%